Humanitarian Leadership: A Research Protocol to Evaluate the Effectiveness of a Leadership Training Program Aimed at Enhancing Leadership Skills for Humanitarians. (2019) - Bollettino, Vincenzo; Kenney, Allyson Brown; Schwartz, Sarah; Burnham, Gilbert
No abstract available